Application of Relaxation Guide Imagery Murrotal Al-Qur’an in Patients with Acute Pain Disorders - putri, zhavira; Rochmayanti; Widodo, Wasis (Development Nursing Research, 2026)
Abstract Background: The need for comfort is a state that makes a person feel comfortable, protected from psychological threats, free from pain, especially pain. Pain management can be done with two approaches, namely pharmacological and non-pharmacology. Based on Katherine Kolcaba's theory, the function of the nurse that emphasizes the importance of providing comfort holistically includes physical, psychospiritual, sociocultural, and environmental dimensions. The application of relaxation of the Qur'anic murrotal imagery guide is carried out to calm the mind, reduce emotional and physical tension so as to provide comfort, overcome pain, stress or anxiety. Methods: Using a descriptive method in the form of a case study with 2 respondents focusing on the implementation of guided imagery therapy and Qur'an murrotal therapy was carried out 2 times in 1 day for 3 days with a time of about ±10-15 minutes each session with the NRS (Numeric Rating Scale) measurement evaluation sheet scale. Results: Research shows that after the implementation of relaxation of the Qur'an's murrotal imagery guide There was a decrease in the pain scale as evidenced on the 3rd day of Mr.S from scale 2 (mild pain) to scale 0 (no pain) and Mrs. W from scale 1 (mild pain) to scale 0 (no pain), It can be done independently with 2x for 15 minutes. Conclusions: The application of relaxation therapy guided imagery and murrotal Al-Qur'an in patients with acute pain disorders is effective in reducing pain, in this case where the role of the nurse function is able to provide positive things in nursing interventions independently, especially in meeting physical and psychological needs, providing comfort in an effort to suppress the stimulation of patients with pain disorders in accordance with the concept of pain and comfort Kolcaba (Comfort Theory)